Evaluasi Kebijakan Penanganan Covid-19 Di Kota Surabaya: Studi Kasus Kebijakan PSBB - Zamzam Isnan Nasution (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
This research enriches the existing debate by taking a study to evaluate the policy for handling the Covid-19 pandemic in the City of Surabaya based on the Health Quarantine Law. The research question to be raised is how the Regional Government of Surabaya City implements the policy options available in the Quarantine Law in order to reduce the rate of spread of Covid-19 in its jurisdiction. Surabaya City Government can be said to have adequate financial resources and work programs to carry out tracking, tracing and testing of the population in the city of Surabaya. However, although formally a number of institutional aspects have been designed, there are still several obstacles, namely the ineffective use of the budget and the behavior of individuals who are less aware of the threat of Covid-19. This study suggests the need for massive institutional penetration to break the chain of disease spread by involving community participation.